Kinetic and Equilibrium Analysis of Tartrazine Photocatalytic Degradation Using Iron-Doped Biochar from Theobroma cacao L. Husk via Microwave-Assisted Pyrolysis - Jean Espinoza; Elvia V. Cabrera; Ullrich Stahl; Jhonny Correa-Abril (Chemistry Proceedings, 2024)
The MAP process involved placing acid-pretreated biomass (CPH) in a domestic microwave oven at 600 W for 15 min. This was followed by a doping process with iron salts (+2, +3) to obtain BCCPH-Fe. Characterization of BCCPH-Fe was carried out using surface analysis (BET), TGA analysis and FTIR. Subsequently, the photodegradation process was performed using three different light sources (solar, UV 254 nm and UV 356 nm), with tartrazine as the adsorbate. The effect of pH on photodegradation was studied, and the percentage of degradation was evaluated through equilibrium and kinetic studies. The amount of BCCPH-Fe, tartrazine concentration, and exposure time to the light source were also evaluated. The best conditions for the photodegradation process were: light source was 254 nm, pH of 5, 1 g of BCCPH-Fe over 100 mL of tartrazine, 25 ppm tartrazine concentration, and 40 h exposure time. Under these conditions, a 93.45% removal of tartrazine was achieved. The experimental data of the adsorption equilibrium best fit the Langmuir-Hinshelwood model, while the adsorption kinetics best fit the pseudo-first-order model. The apparent kinetic constant was 0.04053 [h−1], and the correlation coefficient was 0.98667. In conclusion, photodegradation using BCCPH-Fe can be an effective method for the removal of tartrazine from wastewater, offering a sustainable alternative to traditional methods.